Enterprise API management design and deliver valuable business APIs - Weir, Luis (Expert insight., 2019)
Enterprise API Management shows how to define the right architecture, implement the right patterns, and define the right organization model for business-driven APIs. The book explores the architectural decisions, implementation patterns, and management practices for successful enterprise APIs. And it gives clear, actionable advice on choosing ...